2015
DOI: 10.5588/ijtld.14.0500
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Xpert<SUP>®</SUP> MTB/RIF assay for the diagnosis of extra-pulmonary tuberculosis in South Korea

Abstract: The Xpert assay showed acceptable sensitivity in certain groups and excellent specificity in diagnosing EPTB and detecting RMP resistance in an intermediate TB burden country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 1 publication
1
32
0
1
Order By: Relevance
“…Data on Xpert performance in CSF in adults are limited to reports of small numbers of meningitis patients in extra-pulmonary TB cohorts 10–18 , multiple meta-analyses 9,19,20 , and two well-conducted TBM cohort studies. 21,22 In South Africa, Patel et al found 67% sensitivity with Xpert in microbiologically proven TBM.…”
Section: Introductionmentioning
confidence: 99%
“…Data on Xpert performance in CSF in adults are limited to reports of small numbers of meningitis patients in extra-pulmonary TB cohorts 10–18 , multiple meta-analyses 9,19,20 , and two well-conducted TBM cohort studies. 21,22 In South Africa, Patel et al found 67% sensitivity with Xpert in microbiologically proven TBM.…”
Section: Introductionmentioning
confidence: 99%
“…The studies also used different culture references. Nine studies only used BACTEC MGIT 960 liquid culture as the reference, one study only used Lowenstein-Jensen solid culture as the reference [34], and four studies used both of them as references [18,22,24,35]. The performances of BACTEC MGIT 960 liquid and Lowenstein-Jensen solid cultures were different [54], which might also be one of the sources of heterogeneity among the studies.…”
Section: Discussionmentioning
confidence: 99%
“…The kappa index of agreement for the selection and data extraction was 0.877 (95% CI, 0.779-0.975) between the two investigators. Only two studies were conducted in high-income countries [18,35], while the rest were conducted in low-and middle-income countries. Fifteen articles were written in English and eleven in Chinese.…”
Section: Identification Of Studies and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with suspected tuberculosis, the final diagnosis was identified by the retrospective medical record review and classified into tuberculosis and non-tuberculosis. The final diagnosis of tuberculosis was made based on radiological and clinical improvement after 6 months of standard anti-tuberculosis therapy [10,13]. The standard therapy was defined according to guidelines as an intensive phase, consisting of isoniazid, rifampin, ethambutol, and pyrazinamide, followed by a continuation phase, consisting of isoniazid, rifampin, and ethambutol.…”
Section: Definition Of Tuberculosis and Non-tuberculosismentioning
confidence: 99%